Impact of Serum Procalcitonin on Duration of Mechanical Ventilation and ICU Stay in Post-Cardiopulmonary Bypass Patients - Islam, Mohammad Azizul; Samad, Md Abdus; Bristy, Rokhsana Akter; Raju, Mezanur Rahman; Islam, Md Rabiul; Tamal, S M Taslim Yusuf (KYAMC Journal, 2025)
Background: Post-cardiopulmonary bypass (CPB) patients often experience systemic inflammatory responses, with serum procalcitonin (PCT) serving as a biomarker for postoperative complications. Objective: To evaluate the impact of serum Procalcitonin (PCT) levels on mechanical ventilation duration and Intensive Care Unit (ICU) stay in patients undergoing Cardiopulmonary Bypass (CPB). Materials and Methods: This prospective observational study was conducted in the Department of Cardiac Surgery, National Heart Foundation Hospital and Research Institute, Dhaka, Bangladesh, from September 2020 to August 2022. It included 140 patients who underwent cardiac surgery with cardiopulmonary bypass in the cardiac surgery department at the National Heart Foundation Hospital and Research Institute. Results: In this study, patients were divided into two groups- group A included 70 patients with serum procalcitonin levels <7 ng/ml and group B included 70 patients with serum procalcitonin levels>7 ng/ml. On 1st postoperative day, serum procalcitonin levels were 1.36(±0.97) ng/ml and 27.09(±26.11) ng/ml in groups A &B respectively (p < 0.001).Group B had significantly prolonged mechanical ventilation time (18.0 ± 16.5 hours vs. 8.4 ± 2.0 hours, p < 0.001) and longer ICU stays (40.8 ± 32.7 hours vs. 23.1 ± 3.6 hours, p < 0.001) compared to Group A. Total hospital stay was also extended in Group B (8.5 ± 2.6 days vs. 7.2 ± 0.7 days, p < 0.001). Conclusion: Elevated postoperative serum procalcitonin levels are associated with prolonged mechanical ventilation, extended ICU stays and longer hospitalization in CPB patients. Monitoring PCT levels may help predict recovery trajectories and guide early interventions to improve postoperative outcomes. KYAMC Journal Vol. 16, No. 01, April 2025: 3-8